2019
DOI: 10.3892/ol.2019.11117
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the effects of microRNA‑23a‑3p on pancreatic cancer and its underlying molecular mechanism

Abstract: Previous studies have demonstrated that microRNA (miR)-23a-3p plays a role as an oncogene that is involved in several different types of carcinoma. However, few studies investigated the association between miR-23a-3p and pancreatic cancer (PC). The aim of the present study was to elucidate the biological functions of miR-23a-3p in PC and to investigate its underlying molecular mechanisms. The expression of miR-23a-3p in PC and adjacent normal tissues was investigated using microarrays. In order to validate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Their binding relationship was ascertained by RNA pull‐down, while the binding site was validated by dual‐luciferase reporter gene assay. Moreover, miR‐23a‐3p has been reported to function as an oncogenic regulator of pancreatic cancer 12 . Existing literature has reported that FOXO3 is poorly expressed in pancreatic cancer, thus signifying its vital significance in tumorigenesis and cancer development, 36 which was consistent with our finding.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Their binding relationship was ascertained by RNA pull‐down, while the binding site was validated by dual‐luciferase reporter gene assay. Moreover, miR‐23a‐3p has been reported to function as an oncogenic regulator of pancreatic cancer 12 . Existing literature has reported that FOXO3 is poorly expressed in pancreatic cancer, thus signifying its vital significance in tumorigenesis and cancer development, 36 which was consistent with our finding.…”
Section: Discussionsupporting
confidence: 91%
“…The results of dual‐luciferase reporter assay indicated that miR‐23a‐3p mimic inhibited the luciferase activity of LINC00472‐WT without altering that of LINC00472‐MUT (Figure 4D). Meanwhile, a high expression pattern of miR‐23a‐3p was reported in pancreatic cancer 12 . Therefore, we speculated that LINC00472 may regulate the development of pancreatic cancer through miR‐23a‐3p.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Fan’s study showed that a higher FLR was significantly related to poor OS and DFS for ESCC ( 38 ). In ECC, Ji’s study showed that an increased NLR was related to poor prognosis for patients with DCC ( 39 ), and Lin’s study showed that a high LMR could predict poor prognosis in patients with PCC after R0 radical resection ( 11 ). However, these were not studies comparing the prognostic power of inflammatory indicators for ECC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we assumed that the regulation of RUNX2 on vascular injury repair might be achieved through regulating the expression of miR-23a. In addition, TGF-β receptor type II (TGFBR2), a predicted target gene of miR-23a, is important for cell proliferative and apoptotic potential (11). A recent study has demonstrated that TGFBR2 is implicated in the proliferation of smooth muscle cells (SMCs) after arterial injury, including the relevant repair process (12).…”
Section: Introductionmentioning
confidence: 99%